Ferroin in dyes degradation by Fenton-like process: a chemical waste recycling perspective - William Bardelin Nunes (IWA Publishing, 2021)
Published literature describes the formation of the Fe (II)–phenanthroline complex (ferroin) as a stop way for Fenton processes, reducing radical yield. By contrast, this study presents evidence that ferroin can be activated by UVA in mildly acidic media in a photo-Fenton-like process. Because ferroin is the main waste from total iron determination in environmental samples, a recycling approach is suggested. Based on the best practices of waste management planning, an application of the proposed method for treating another chemical waste is presented. Titrimetric ammonia determination waste containing 2.67 mg L−1 methyl red azo dye and 1.33 mg L−1 methylene blue was degraded using the optimized experimental conditions: pH = 5.2–5.4; [H2O2] = 310 mg L−1; [ferroin] = 1.4 mg L−1; temperature = 36 ± 1 °C; reaction time = 165 min under UVA irradiation. Attenuation of most intense spectroscopic bands for the dyes achieved 94% (510 nm) and 96% (665 nm) reduction for methyl red and methylene blue, respectively, with degradation of ferroin itself. The present work brings empirical evidence that is possible to recycle ferroin as photo-Fenton-like process catalyst, as well as determine the best conditions for providing less acidic treated effluents with negligible suspended solid concentration, better than that obtained from classical photo-Fenton processes. HIGHLIGHTS Ferroin can act as a catalyst in photo-Fenton-like processes.; Degradation of azodye by modified Fenton treatment.; Drawbacks from classical Fenton processes are mitigated.; Waste acting as a catalyst for treating another waste.; Improvement for institutional waste management plan.;